2016
DOI: 10.1111/wrr.12457
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing the combination of a polymeric membrane dressing plus negative pressure wound therapy against negative pressure wound therapy alone: The WICVAC study

Abstract: Negative pressure wound therapy (NPWT) is the treatment of choice for chronic wounds; yet, it is associated with considerable workload. Prompted by its nonadhesive and wound-healing properties, this study investigated the effect of an additional polymeric membrane interface dressing (PMD; PolyMem WIC) in NPWT. From October 2011 to April 2013, 60 consecutive patients with chronic leg wounds or surgical site infections after revascularization of lower extremities were randomly allocated to either treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Data now show a direct link between compromised skin barrier and subsequent wound recurrence, 39 a significant consideration for chronic wound management. Although several clinical studies have demonstrated enhanced wound closure and faster granulation with tNPWT, 40 , 41 few studies have performed follow-up assessments to determine rates of wound recurrence. 42 A future preclinical in vivo investigation would provide a unique opportunity to explore recurrence, an important and often overlooked aspect of wound healing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Data now show a direct link between compromised skin barrier and subsequent wound recurrence, 39 a significant consideration for chronic wound management. Although several clinical studies have demonstrated enhanced wound closure and faster granulation with tNPWT, 40 , 41 few studies have performed follow-up assessments to determine rates of wound recurrence. 42 A future preclinical in vivo investigation would provide a unique opportunity to explore recurrence, an important and often overlooked aspect of wound healing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Vacuum sealing drainage can completely seal the wound and reduce the probability of cross infection in the surrounding tissues of patients. And continuous negative pressure suction can effectively remove the exudate and necrotic tissue of the wound, improve microcirculation of the wound and eliminate tissue edema [7,8]. Ilizarov technique can completely remove the necrotic bone segments without re-repair of bone and soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Independent researchers have found that this unique pore structure allows PolyMem to absorb fluids almost instantly while completely avoiding ingrowth of tissue into the dressing, features not tested in this study. [12,21,29,30] 4. Both test dressings outperformed PolyMem on strength and stretch tests.…”
Section: How the In Vitro Test Results Translate To Real-world Clinic...mentioning
confidence: 99%
“…[1,2,5,19,20] PolyMem's multiple components work synergistically with each other and with the body. [5,7,12,21,22] When used appropriately, PolyMem delivers all of the benefits mentioned in the article, including extra absorption, non-adherence to the wound bed, conforming to the wound, controlling inflammation, and promoting brisk wound healing, even when used on challenging wounds, such as chronic diabetic foot ulcers. [5,7,12,22,23]…”
Section: Introductionmentioning
confidence: 99%